Optimasi Gom Xanthan dan Natrium Karboksimetilselulosa terhadap Mutu Fisik dan Laju Pelepasan Gel Meloksikam In Vitro (Optimization of xanthan gum and Carboxymethylcellulose Sodium on Physical Characteristic and In Vitro Release of Meloxicam from Gel) - Rizka Kurnia Cetika; Lidya Ameliana; Lina Winarni (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
The aims of this study was to develop and optimize the composition of xanthan gum, carboxymethylcellulose sodium and combination of both that fulfilled the desired requirements in the preparation of meloxicam gel. The prepared gels were evaluated in term of appearance, pH, spreadibilty, viscosity, rheological properties, homogenity and in vitro drug release of meloxicam. The gel was optimized using simplex lattice design method. Influence of gelling agent xanthan gum and carboxymethylcellulose sodium were also investigated. The data was analyzed by statistic program of design expert software trial version 9.0.3.1. All of the evaluation that has been done has fulfilled the optimum requirements desired. The optimal formulation was found the number of xanthan gum is 0.060 – 3 grams and CMC Na is 0.144 – 3 grams in every 100 grams of gels. Keywords: gel, meloxicam, xanthan gum, carboxymethylcellulose sodium